Chicken DDX1 Acts as an RNA Sensor to Mediate IFN-β Signaling Pathway Activation in Antiviral Innate Immunity - Lin, Zhenyu; Wang, Jie; Zhu, Wenxian; Yu, Xiangyu; Wang, Zhaofei; Ma, Jingjiao; Wang, Hengan; Yan, Yaxian; Sun, Jianhe; Cheng, Yuqiang (Frontiers in Immunology, 2021)
Chickens are the natural host of Newcastle disease virus (NDV) and avian influenza virus (AIV). The discovery that the RIG-I gene, the primary RNA virus pattern recognition receptor (PRR) in mammals, is naturally absent in chickens has directed attention to studies of chicken RNA PRRs and their functions in antiviral immune responses. Here, we identified Asp-Glu-Ala-Asp (DEAD)-box helicase 1 (DDX1) as an essential RNA virus PRR in chickens and investigated its functions in anti-RNA viral infections. The chDDX1 gene was cloned, and cross-species sequence alignment and phylogenetic tree analyses revealed high conservation of DDX1 among vertebrates. A quantitative RT-PCR showed that chDDX1 mRNA are widely expressed in different tissues in healthy chickens. In addition, chDDX1 was significantly upregulated after infection with AIV, NDV, or GFP-expressing vesicular stomatitis virus (VSV-GFP). Overexpression of chDDX1 in DF-1 cells induced the expression of IFN-β, IFN-stimulated genes (ISGs), and proinflammatory cytokines; it also inhibited NDV and VSV replications. The knockdown of chDDX1 increased the viral yield of NDV and VSV and decreased the production of IFN-β, which was induced by RNA analog polyinosinic-polycytidylic acid (poly[I:C]), by AIV, and by NDV. We used a chicken IRF7 (chIRF7) knockout DF-1 cell line in a series of experiments to demonstrate that chDDX1 activates IFN signaling via the chIRF7 pathway. Finally, an in-vitro pulldown assay showed a strong and direct interaction between poly(I:C) and the chDDX1 protein, indicating that chDDX1 may act as an RNA PRR during IFN activation. In brief, our results suggest that chDDX1 is an important mediator of IFN-β and is involved in RNA- and RNA virus-mediated chDDX1-IRF7-IFN-β signaling pathways.